(untitled) (Veterinary Science, 2017)
Two kittens were admitted with bilateral congenital tarsal abnormalities. We decided they should both undergo surgical treatment at an early age. Surgical treatment consisted in transarticular External Skeletal Fixation (ESF) for a period of 3 to 4 weeks. Shortly after ESF removal both patients re-gained tarsal mobility, remaining stable with adequate functionality. One patient had two coexisting developmental orthopedic pathologies